Desain Buku Ajar Bahasa Inggris Berdasarkan Model Addie Pada Program Studi Non-Bahasa Inggris - Inayah, Arin; Dimas Priagung Banar Syahputra (Jurnal Bina Ilmu Cendekia, 2025)
English language learning in higher education plays a crucial role in supporting students' academic and professional readiness, especially in the era of globalization. However, students from non-English majors often face difficulties due to teaching materials that are not aligned with their contexts and specific needs. The available textbooks tend to be generic and do not adequately support meaningful and applicable learning. Therefore, it is necessary to develop a contextual English textbook based on the ADDIE model that is relevant to the needs of students across various disciplines. This study aims to design an English textbook using the ADDIE model for non-English study programs at Universitas PGRI Banyuwangi. The research employs a Research and Development (R&D) approach. Based on the results of questionnaires, interviews, and documentation, it was found that approximately 85% of students from non-English majors are at a beginner level in English proficiency. Nevertheless, 90% of them are highly motivated to improve their English skills to an advanced level in order to meet academic and career demands. Regarding learning material needs, around 88% of students expressed the need for content that is relevant to their respective majors and professional fields. The preferred types of materials include authentic texts (75%), new vocabulary (68%), and context-based exercises (70%). Students' preferences for learning activities also revealed clear tendencies. About 80% preferred pair or group discussions, while 85% expected an active and collaborative classroom atmosphere. In addition, 78% of students stated that receiving direct feedback from lecturers is very important in the learning process. In terms of learning outcomes, 82% of students were able to translate texts relevant to their major, 76% could identify academic text types, and 74% showed improvements in reading and speaking skills. The findings also indicate that 92% of students experience a gap between their initial abilities and the expected level of English proficiency. Therefore, it is essential to develop a textbook based on needs analysis and the contextual ADDIE model to bridge this gap and provide a more relevant and meaningful learning experience for students across disciplines.